Digital Financial Transactions Using QRIS Reviewed From The Legal Aspects - Wongsowinoto, Fridayani; CUACA, BENNY (Politeknik Negeri Bengkalis, 2024)
One sector that is experiencing changes in the current digital era is the financial sector, where payment transactions are starting to be carried out through digital systems, some of which use the QRIS system. Payment transactions via QRIS can speed up transactions and reduce operational costs, especially for commercial players. However, the use of QRIS has clearly given rise to what is called digital crime, which can harm users (QRIS consumers) by destroying the QR code and